A rhetorical analysis of 1 Timothy 2:9-15 with a special focus on the role of women in the church - Williams, Allan Alexander (Rhodes University, Faculty of Divinity, Department of Divinity, 1992)
This thesis investigates the role of women in the early church as portrayed in 1 Timothy 2:9-15 using the recently-developed method of Rhetorical Analysis. It makes use of a rhetorical approach largely based on the method proposed by Kennedy, supplemented by insights from scholars who have emphasised the argumentative element in rhetoric. This method illustrates how the role of women in the church is decisively determined by the argument in the letter as a whole. A brief survey of classical rhetoric is given. The typical structure of a rhetorical discourse is listed with its component sections. The validity of using rhetorical analysis as a means for interpreting New Testament texts is justified. Textual units are identified from the structure of the text. Rhetorical insights are used to explain how the identified units cohere within the overall structure of the letter and how they relate to one another and interact. The thesis is developed that the section on women and teaching can only be meaningfully investigated in the light of the text as a whole and of the motifs in the letter. The thesis has a special focus on 2:9-15. This section is analysed in more detail than the rest of the text with the exception of 1 Timothy 1. As exordium, the latter provides the introduction to the situation dealt with in the letter, introduces the case, and sets the tone for the rest of the letter. The persuasive power of rhetoric in any situation depends to a large extent on its use of common tradition. The socio-cultural setting of the author is consequently analysed. Finally, the role of women in Graeco-Roman society is analysed in terms of motifs found in 1 Timothy 2:9-15.
Keywords: Bible -- Criticism, interpretation, etc.; Women in the Bible; Women in Christianity -- History -- Early church, ca. 30-600; Women in Christianity; Sexism in religion